1990
DOI: 10.1097/00132586-199010000-00035
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia for Hemorrhoidectomy. A Comparison Between Caudal and Local Infiltration

Abstract: This study compared the analgesic eflectiseness of local injiltration of bupivacaine with caudal extradural bupivacaine in thejirst 48 hours ufter haemorrhoidectomy. Surgical and anaesthetic protocol was rigidly standardised. The caudal group had significantly less pain in the Jirst 6 hours after haemorrhoidectomy. and on jirst bowel opening, when compared to those who received local infiltration of bupivacaine. There was no signi$cant difference between the two groups with respect to further analgesic require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Another study26 compared caudal epidural bupivacaine versus local wound infiltration with bupivacaine after induction of general anaesthesia. Pain scores were significantly lower with the caudal epidural group compared with the local infiltration group on awakening and at 3 h (both P < 0·05), at 6 h ( P < 0·01) and at first bowel action ( P < 0·05), but not at 12, 24 and 48 h or on pack removal.…”
Section: Resultsmentioning
confidence: 99%
“…Another study26 compared caudal epidural bupivacaine versus local wound infiltration with bupivacaine after induction of general anaesthesia. Pain scores were significantly lower with the caudal epidural group compared with the local infiltration group on awakening and at 3 h (both P < 0·05), at 6 h ( P < 0·01) and at first bowel action ( P < 0·05), but not at 12, 24 and 48 h or on pack removal.…”
Section: Resultsmentioning
confidence: 99%
“…Haemorrhoidectomy involves surgery on the sensitive anoderm, which is rich in nerve endings. Over the years, several possible ways of reducing pain and discomfort after this day‐care operation have been proposed, including use of multimodal analgesia5, 14–31, reducing postoperative anal spasm32–34, restricting surgery to one haemorrhoid at a time35, avoiding a closed technique36, use of bulky adherent dressings37, rectal application of metronidazole38, pre‐emptive analgesia3, 17, 39–43, diathermy dissection44, 45, caudal block8, 46, preoperative lactulose47, pudendal40, 48 and perineal11, 41, 42, 49, 50 blocks, stapled anopexy1, 51–63, Doppler‐guided haemorrhoid artery ligation64–74 and detailed counselling with a line of communication to the hospital5. Some of these are of doubtful value on their own48, 75, 76.…”
Section: Discussionmentioning
confidence: 99%
“…A further evolution in technique is day‐care open haemorrhoidectomy under local anaesthesia (LH). Although this has been reported previously6–11, there is a paucity of randomized controlled trials to support its routine use.…”
Section: Introductionmentioning
confidence: 88%
“…[1][2][3][4][5] In prior studies, local anesthetics (bupivacaine), antiinflammatory drugs (NSAIDs), and nitrates (glyceryl trinitrate, 0.2%) have been evaluated for reducing pain after a hemorrhoidectomy. [6][7][8][9][10] These studies indicated some limitations with these medications such as short duration of action and serious side effects. Metronidazole, especially in topical form, has been more effective in reducing pain.…”
Section: Introductionmentioning
confidence: 99%